The detection and prevention of adverse drug events in nursing home and home care patients: Study protocol of a quasi-experimental study - Langenberger, Benedikt; Baier, Natalie; Hanke, Frank-Christian; Fahrentholz, Jacqueline; Gorny, Christina; Sehlen, Stephanie; Reber, Katrin Christiane; Liersch, Sebastian; Radomski, Ralf; Haftenberger, Jens; Busse, Reinhard; Vogt, Verena; et al. (Nursing Open, 2022)
Aim: To estimate the cost-effectiveness of an intervention facilitating the early detection of adverse drug events through the means of health professional training and the application of a digital screening tool. Design: Multi-centred non-randomized controlled trial from August 2018 to March 2020 including 65 nursing homes or home care providers. Methods: We aim to estimate the effect of the intervention on the rate of adverse drug events as primary outcome through a quasi-experimental empirical study design. As secondary outcomes, we use hospital admissions and falls. All outcomes will be measured on patient-month level. Once the causal effect of the intervention is estimated, cost-effectiveness will be calculated. For cost-effectiveness, we include all patient costs observed by the German statutory health insurance. Results: The results of this study will inform about the cost-effectiveness of the optimized drug supply intervention and provide evidence for potential reimbursement within the German statutory health insurance system.
CRIS-Team Scopus Importer:2022-09-26
Keywords: adverse drug events; home care intervention; hospital admissions; nursing home intervention; quasi-experimental study design